Influence of a Moderate-Intensity Exercise Program on Early NK Cell Immune Recovery in Pediatric Patients After Reduced-Intensity Hematopoietic Stem Cell Transplantation. (December 2017) - Chamorro-Viña, Carolina; Valentín, Jaime; Fernández, Lucía; González-Vicent, Marta; Pérez-Ruiz, Margarita; Lucía, Alejandro; Culos-Reed, S. Nicole; Díaz, Miguel Ángel; Pérez-Martínez, Antonio
Introduction: After allogeneic hematopoietic stem cell transplantation (HSCT), NK cell reconstitution, which is crucial for positive outcomes, is dominated by the CD56 bright subset with low NK cell cytotoxicity (NKCC) activity. Moderate exercise has been described as a potent NK cell stimulus in adults with cancer.Purpose: To determine the effects of a moderate-intensity exercise program on NK cell recovery early after HSCT and the feasibility of this intervention.Methods: Six children undergoing allogeneic HSCT were randomized to an exercise program (EP) or control (CT) group. The EP group performed a 10-week training combining in-hospital and home-based EP.Results: We observed a significant increase in the posttraining/pretraining ratio of the CD56 dim subset (EP = 1.27 ± 0.07; CT = 0.99 ± 0.08; P < .005) of the EP group. The ratio of NKCC was 8 times greater in the EP group.Conclusion: Data suggest that a moderate-intensity EP program performed early after HSCT is feasible and might redistribute the CD56 dim /CD56 brigh NK cell subset, improving NKCC. The results are still preliminary and must be interpreted with caution.